Removal of a dye used in the textile industry using avocado seed Hass variety as a bio-adsorbent (LACCEI, 2024)
Arequipa is a Peruvian city that produces a significant amount of avocado. This generates a significant amount of avocado seeds that are discarded without any use. The present research proposes Hass avocado seed as a promising bio-adsorbent of a textile dye (Novacron Navy FNB) from contaminated water at laboratory scale. The percentage of dye removal by avocado seed powder was studied taking into account the effect of factors of interest in the adsorption processes such as pH, bio-adsorbent dosage and particle size. Adsorption kinetics and Zero Charge Point were evaluated. The results show that avocado seed powder removes 97.46 % of a 100 mg/L Novacron Navy FNB solution at pH=2, a dose of 1 g/25 mL and a particle size of 75-150 μm. The adsorption process was adjusted to pseudo-second order kinetics with the limiting factor being chemisorption. The point of zero charge was pHPZC=5.5 and considering that adsorption process is better at pH=2, it can be said that one of the bio-adsorption mechanisms of this process would be electrostatic attraction. This study has demonstrated that the Hass avocado seed is a renewable resource with dye adsorption capacity and can be tested to evaluate its removal capacity in textile wastewater, since it is an abundant and low-cost waste.